Sustainable Hotel Finance: Green Leadership and Governance Integration - Julia Safitri; Zulkifli Sulthan; Syarief Gerald Prasetya (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
Environmental and sustainability issues are becoming increasingly urgent in today’s global business. The rapidly growing hospitality industry in Indonesia faces significant challenges in integrating green leadership principles into financial management to achieve sustainable business performance. This study aims to empirically examine the influence of green leadership on sustainable financial management, as well as the moderating role of governance within the hospitality sector. A quantitative approach was adopted, with data collected through structured questionnaires distributed to 150 hotel respondents across various regions in Indonesia. Purposive sampling was employed to select respondents with decision-making authority in sustainability-related practices. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the research hypotheses. The results unveiled that green leadership significantly influenced sustainable financial management in the hospitality industry. Furthermore, governance played a moderating role, strengthening this relationship. Specifically, strategic governance practices such as transparency, accountability, and ethical compliance enhanced the positive impact of green leadership on sustainability performance. This study provides practical implications for hospitality industry players, highlighting the importance of fostering proactive green leadership and implementing effective governance mechanisms as essential steps to address environmental pressures and achieve long-term business sustainability.